Neuropsychological performance of methadone-maintained opiate users. (August 2014) - Wang, Grace Y; Wouldes, Trecia A; Kydd, Rob; Jensen, Maree; Russell, Bruce R
Methadone maintenance treatment (MMT) has been used to treat opiate dependence since the mid-1960s. Previous studies have investigated the effects of methadone on cognitive function however the findings have been inconsistent. Some report a complete absence of deficits while others report different types of cognitive impairment. Our research aimed to investigate the effects of MMT on cognitive function by comparing the performance of patients currently enrolled in MMT ( n =32) with opiate-dependent subjects ( n =17) and healthy control subjects ( n =25) on a computerised neuropsychological test battery. Both the patients undertaking MMT and the opiate users showed less efficient interaction between visual searching and manually connecting digits and letters during the Switching of Attention Task than the healthy control subjects ( F (2, 64)=3.25, p =0.05), which indicates deficits in information processing. Nevertheless, the performance of the MMT group was similar to that of healthy control subjects in all other tasks, in contrast to the group of opiate users who performed poorly when compared to healthy control subjects during tests of attention (mean difference (MD)=2.8, 95% confidence interval (CI) (0.9–4.7), p =0.001) and executive function (MD=5.9, 95% CI (1.3–10.5), p =0.007). These findings suggest that cognitive function in patients undertaking MMT is improved compared to those dependent on illicit opiates.